Differences In The Effectiveness Of Green Belt Leaf Boiled Water And Soursop Leaves On Which White In Adolescent Girls At SMAN 4 Serang City, Banten, 2023 - Uli Anitasari Matanari; Tetin Rismayanti (CV. Inara, 2024)
In Indonesia, the problem most often experienced by young women is vaginal discharge. In medical circles, vaginal discharge is known as leukorrhea or fluor albus, which is a discharge from the vagina. Vaginal discharge is a candida fungal infection in female genitalia and is caused by organisms such as yeast, namely candida albicans. Under normal circumstances, the vagina produces fluid that is clear, odorless, colorless, not excessive in quantity and not accompanied by itching. Vaginal discharge is the most common complaint found in women. Vaginal discharge can occur in normal circumstances (physiological), but can also be a symptom of a disorder that must be treated (pathological). The research used was a Quasy Experiment type of research to determine the difference in the effectiveness of giving boiled water from green betel leaves and soursop leaves on vaginal discharge in young women at SMA Negeri 4 Serang Banten with a Two Group Pretest - Posttest research design. Respondents were divided into 2 groups, namely the betel leaf group and the soursop leaf group, each group numbering 45 people. With univariate and bivariate analysis. With the results of the Wilcoxon test, which obtained a significance value of 0.001 (p<0.05), it can be concluded